Pengaruh Persepsi Siswa tentang Penerapan Metode Tutor Sebaya, Lingkungan Belajar dan Motivasi Belajar Siswa terhadap Efektivitas Metode Pemecahan Masalah dan Hasil Belajar Siswa Ranah Kognitif pada Kelas I MI Al Hikmah Ngareskidul Gedeg Mojokerto - Achmad Padi (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
The purpose of this study are: 1) To determine whether the effect Implementation Method Student Perceptions of the Effectiveness of Peer Tutor troubleshooting methods. 2) To determine whether the learning environment affect the effectiveness of troubleshooting methods. 3) To determine whether the Student Motivation affect the effectiveness of troubleshooting methods. 4) To determine whether the Student Perceptions of Peer Tutor Application Method to cognitive learning outcomes of students. 5) To determine whether the learning environment affect the students' cognitive learning outcomes. 6) To determine whether the Student Motivation towards cognitive learning outcomes of students. 7) To determine whether the Student Perceptions of Peer Tutor Application Method, learning environment, Student Motivation affect the effectiveness of troubleshooting methods. 8) To determine whether the Student Perceptions of Peer Tutor Application Method, learning environment, Student Motivation effect on students' cognitive learning outcomes. From the analysis can be summarized as follows: 1) There is a significant relationship between Student Perceptions of Peer Tutor Application Method, learning environment, Student Motivation Method of the Effectiveness of troubleshooting. with the value Fhitung 77 978 (significance F = 0. 000). So Fhitung> Ftabel (77 978> 1. 69) or Sig F <5% (0. 000 <0. 05). This means that together the independent variables consist of variables Student Perceptions about the application of the method tutor Peer (X1), the Learning Environment (X2), Student Motivation (X3) simultaneously to variable Efektiftas Solving Methods of Problem Solving (Y1) 2) There is a significant relationship between student Perceptions of Peer Tutor Application method, learning environment, student Motivation towards learning outcomes of students cognitive value Fhitung 78 323 (significance F = 0. 000). So Fhitung> Ftabel (78 323> 1. 69) or Sig F <5% (0. 000 <0. 05). This means that together the independent variables consist of variables Student Perceptions of Peer tutor application method (X1), the Learning Environment (X2), Student Motivation (X3) simultaneously to variable Learning Outcomes Cognitive Domains (Y2).